TRADE AND ECONOMIC COOPERATION BETWEEN THE RUSSIAN FEDERATION AND THE REPUBLIC OF COTE D'IVOIRE - N. Sekongo (Publishing House of the State University of Management, 2017)
The article examines some indicators that characterize the role of Côte d'Ivoire in the global economic system. Special attention is paid to the trade and economic cooperation between Russia and Côte d'Ivoire. The main areas of partnership between countries of strategic importance are shown. The indicators of development of foreign trade between the countries are analyzed, which testify to the long-term development of cooperation.